An awareness study on the management of food quality in the Malaysian food industries / Halimahton Zahrah Mohd. Som, Norizzah Abd. Rashid and Siti Noorbaiyah Ab. Malek - Mohd. Som, Halimahton Zahrah; Abd. Rashid, Norizzah; Ab. Malek, Siti Noorbaiyah (1998)
This study was conducted in order to obtain information on the Quality Systems practised in the local food industries. The data obtained from this study were then utilized to study the needs by the local food industries and potential students on the setting up of an Advanced Diploma (Degree) course in Food Quality Management at Institut Teknologi MARA. The surveys were conducted on the local food industries and related government agencies, and potential students. The results obtained from the survey on the "Management of Food Quality in the Malaysian Food Industries" indicated that almost all the respondents applied Quality Systems in their daily operations. Among the Quality Systems, Good Manufacturing Practices or GMP and Hazards Analysis Critical Control Point or HACCP appeared to be the two major systems implemented, followed by ISO 9000s. For most of the respondents, these Quality Systems were being implemented at the processing line, raw material intake, packaging stage and product storage. Besides the production area, the respondents also practised Quality Systems in their management, marketing and distribution, and administration. The survey on the "Feasibility Study on the setting up of an Advanced Diploma (Degree) course in Food Quality Management" indicated that almost all the respondents agreed with the setting up of such course. Most of the potential students surveyed were interested to enrol in this course, which was preferred to be conducted on a full time basis. The respondents felt that the potential candidates must have at least a Diploma in Food Science and Technology while those with Microbiology, Nutrition or Dietetics background could also be considered. The respondents also agreed with the duration of the course suggested, which was 2 years or 4 semesters. All the proposed core subjects on Quality and Quality Management received favourable response from the respondents. The respondents also agreed on the inclusion of Science and Technology subjects, Management subjects, and Industrial Training.